On the Role of the Urey Reaction in Extracting Carbon From the Earth's Atmosphere and Adding It to the Continental Crust - Kellogg, Louise H.; Turcotte, Donald L.; Lokavarapu, Harsha (Frontiers in Astronomy and Space Sciences, 2019)
Urey (1952a,b, 1956) introduced the Urey reaction to explain the origin of carbonates in the continental crust. The reaction extracts CO2 from the atmosphere in acid rain that reacts with calcium silicates, the products are transported to the oceans where organic and inorganic processes results in the deposition of calcium carbonates. The origin of the CO2 can be (1) the early atmosphere and (2) the mantle. The reaction removes almost all the atmospheric CO2 that survived the formation of the Earth. If surface volcanism introduces more CO2 than is lost by subduction, the CO2 entering the atmosphere will be lost to the continental crust by the Urey reaction. Studies of carbon fluxes between surface reservoirs have demonstrated the importance of the Urey reaction in controlling the concentration of CO2 in the atmosphere. At the present time the only surface reservoir with a large mass of carbon is the continental crust. In order to to quantify the rate at which the Urey reaction removes CO2 from the atmosphere we utilize data from the Paleocene-Eocene thermal maximum (PETM). This was a period of elevated global temperatures (SOHT = 4 -5C) at 56 Ma attributed to a pulse of volcanism and associated CO2 in the north Atlantic. We utilize the decay time of this thermal anomaly to quantify the rate at which CO2 is extracted from the atmosphere by the Urey reaction.